Effect of bisphenol F, an analog of bisphenol A, on the reproductive functions of male rats - Asad Ullah; Madeeha Pirzada; Tayyaba Afsar; Suhail Razak; Ali Almajwal; Sarwat Jahan (Environmental Health and Preventive Medicine, 2019)
Abstract Objective Bisphenol A (BPA) is a monomer primarily used in the production of polycarbonate plastic and epoxy resins. Bisphenol F (BPF) is apparently the main BPA replacement that is used increasingly. BPF has been detected in canned food, thermal paper receipts, and soft drinks. In the present experiment, we did both in vitro and in vivo studies to evaluate the effect of low and high-dose BPF exposures on testosterone concentration, oxidative stress, and antioxidants activity in reproductive tissues of male rats. Methods Adult (80–90 days old) male Sprague Dawley rats (n = 36) obtained from the rodent colony of Animal Sciences Department of Quaid-i-Azam University. The direct effects of BPF on the antioxidant enzymes and testosterone secretion were measured in vitro and in vivo studies. In an in vivo experiment, adult male Sprague Dawley rats (n = 42) were exposed to different concentrations of bisphenol F (1, 5, 25, and 50 mg/kg/d) for 28 days. Various biochemical parameters were analyzed including the level of catalase (CAT), superoxide dismutase (SOD), peroxidase (POD), reactive oxygen species (ROS), and lipid peroxidation (LPO). Moreover, sperm motility, daily sperm production (DSP), comet assay, and histological analysis were performed. Results In vitro study showed that BPF exposure significantly (p < 0.05) induced oxidative stress biomarkers, i.e., ROS and LPO, while it did not change antioxidant enzyme and testicular testosterone concentration. Whereas, an in vivo study revealed that BPF induced dose-dependent effect and high-dose (100 mg/kg) exposure of BPF significantly reduced tissue protein (p < 0.05) content, CAT (p < 0.001), SOD (p < 0.05), and POD (p < 0.05) levels while significantly (p < 0.05) augmented ROS and lipid peroxidation. Furthermore, BPF reduces testosterone, LH, and FSH secretion in a dose-dependent manner. Significant (p < 0.001) reduction in plasma and intra-testicular testosterone, LH, and FSH was noticed at 100 mg/kg BFP dose. High-dose exposure reduces spermatogenesis. Conclusion BPF showed an antagonistic effect on male reproductive hormones and induce alterations in testicular morphology. Increased oxidative stress and decreased testicular antioxidant status might be the underlying mechanism of BFP-induced testicular toxicity.